Pedampingan Penyusunan Biaya Produksi Pada Usaha Kreativitas Anak Di Panti Asuhan Kristen Tangmentoe - Marchelin Marchelin; Mince Batara; Stefani Marina Palimbong; Elisabet Pali; Olivia Devi Yulian Pompeng (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2024)
This community service activity aims to provide assistance to the children of the Tangmentoe Orphanage regarding the preparation of production costs in the child creativity business at the Tangmentoe Christian Orphanage where all this time the orphanage children have participated in many skills training to improve creativity, but in determining the selling price following the selling price in the market. In terms of determining the selling price, the production price of each production from the creativity of the orphanage children is needed. By using participatory methods carried out in assisting the preparation of production costs in this activity, the orphanage children have knowledge about the preparation of production costs on all the results of the orphanage children's creativity. And through this activity, orphanage children also have strong motivation in planning to start and manage a business.